Wild Turkeys in Texas : Ecology and Management - Kuvlesky, William P., Jr; Silvy, Nova J.; Mitchell, Brandon M.; Nelle, Steve A.; Bryant, Fred C.; Hilton, Clayton D.; Fritz, Landon C.; Perotto-Baldivieso, Humberto L.; Hardin, Jason B.; Williford, Damon L.; Ortega-S., J. Alfonso; Brennan, Leonard A. (Leonard Alfred) (Book collections on Project MUSE., 2020)
"Bringing together experts on game birds and land management in the state, Wild Turkeys in Texas is the first book in Texas to synthesize the most current information about ecology and management focused exclusively on these three subspecies-the Eastern wild turkey (Meleagris gallopavo silvestris), the Rio Grande wild turkey (M. g. intermedia), and the Merriam's wild turkey (M. g. merriami). Wild Turkeys in Texas addresses important aspects of wild turkey ecology and management in Texas, but its principles are applicable anywhere the Rio Grande, Eastern, and Merriam's turkeys exist. This book marks the continuation of one of the biggest success stories in the research, restoration, and management of the wild turkey in North America"--